Seed quality as a proxy of climate-ready orphan legumes: the need for a multidisciplinary and multi-actor vision - Balestrazzi, Alma; Calvio, Cinzia; Macovei, Anca; Pagano, Andrea; Laux, Patrick; Moutahir, Hassane; Rajjou, Loїc; Tani, Eleni; Chachalis, Dimosthenis; Katsis, Christos; Ghaouti, Lamiae; Gmouh, Said; et al. (Frontiers in Plant Science, 2024)
In developing countries, orphan legumes stand at the forefront in the struggle against climate change. Their high nutrient value is crucial in malnutrition and chronic diseases prevention. However, as the 'orphan' definition suggests, their seed systems are still underestimated and seed production is scanty. Seed priming is an effective, sustainable strategy to boost seed quality in orphan legumes for which up-to-date guidelines are required to guarantee reliable and reproducible results. How far are we along this path? What do we expect from seed priming? This brings to other relevant questions. What is the socio-economic relevance of orphan legumes in the Mediterranean Basin? How to potentiate a broader cultivation in specific regions? The case study of the BENEFIT-Med (Boosting technologies of orphan legumes towards resilient farming systems) project, developed by multidisciplinary research networks, envisions a roadmap for producing new knowledge and innovative technologies to improve seed productivity through priming, with the long-term objective of promoting sustainability and food security for/in the climate-sensitive regions. This review highlights the existing drawbacks that must be overcome before orphan legumes could reach the state of 'climate-ready crops'. Only by the integration of knowledge in seed biology, technology and agronomy, the barrier existing between research bench and local agricultural fields may be overcome, generating high-impact technical innovations for orphan legumes. We intend to provide a powerful message to encourage future research in line with the United Nations Agenda 2030 for Sustainable Development.